Resource redeployment and corporate strategy - Folta, Timothy B.; Helfat, Constance E.; Karim, Samina; Silverman, Brian S.; Emerald eBooks (Bingley, U.K. : Emerald, 2016)
It has been long understood that value creation by corporate strategists is determined by their ability to effectively deploy resources across multiple business units. Recently, scholarly attention has been dominated by studies of "synergy", or sharing resources across businesses. However, a second type of resource deployment, "resource redeployability" or "resource configuration", where resources are withdrawn from one business unit and reallocated to another may not only effect firm value creation, but also firm and industry evolution. This volume advances the resource deployment and synergy debate, and how they differentially affect value and firm decision-making. It clarifies the theoretical determinants and effects of each, revisiting prior work that investigates the benefits of synergy-based strategy, and assessing the benefits of an increased focus on redeployability.
Examining resource redeployment in multi-business firms / Timothy Folta, Constance Helfat, Samina Karim -- Resource redeployment in business ecosystems / Douglas Hannah, Robert Bremner, Kathleen Eisenhardt -- Product turnover: simultaneous product market entry and exit / Douglas Miller, Hsiao-Shan Yang -- Resource redeployment through exit and entry: threats of substitution as inducements / Gwendolyn Lee, Srikanth Parachuri -- Incumbent responses to an entrant with a new business model: resource co-deployment and resource re-deployment strategies / Gautam Ahuja, Elena Novelli -- Resource characteristics and redeployment strategies: towards a theoretical synthesis / Jaideep Anand, Hyunseob Kim, Shaohua Lu -- What goes on beneath the surface of reconfiguration? the impact of redeployment via activity addition and subtraction on firm scope and turnover / Joel Blit, Christopher Liu, Will Mitchell -- The hare and the fast tortoise: dynamic resource reconfiguration and the pursuit of new growth opportunities by Yahoo and Google (1995-2007) / Violina Rindova, Luis Martins, Adrian Yeow -- Linking technologies to applications insights from online markets for technology / Gary Dushnitsky, Thomas Klueter -- Resource reconfiguration: learning from performance feedback / Ari Dothan, Dovev Lavie -- The impact of absorbed and unabsorbed slack on firm profitability: implications for resource redeployment / Josep M. Argile-Bosch, Josep Garcia-Blandon, Monica Martinez-Blasco -- Resource reconfiguration and transactions across firm boundaries: the roles of firm capabilities and market factors / Patia Mcgrath, Harbir Singh.
Includes bibliographical references.
Keywords: Business & Economics -- Strategic Planning; Business strategy; Strategic planning; Electronic books